Knowledge, Attitude and Practices among Public Health Professionals towards COVID-19 in India. (December 2022) - Majumdar, Piyusha; Gupta, S. D.; Sharma, Neeraj; Mangal, D. K.
World is suffering from a pandemic situation due to coronavirus disease (COVID-19) since December 2019. In this emergency, everyone at individual/country/global level is trying to contribute at their best with their available knowledge and resources. However, more and more research and developmental activities are going on but, the reality is far away for a grass-root level health professional. They rely on the indirect sources, that is, published or unpublished literature, social media, internet etc. Many a time, these sources may share an unrealistic or false positive/negative information. Our study was intended to assess the knowledge, attitude and practices related to COVID-19 among the healthcare professionals of different levels. We conducted an online survey after the initiation of the first lockdown in India. Our research team in consultation with the subject experts designed a mix method-based study tool and shared it by sending emails to 1, 200 participants. A total of 180 respondents participated in the online survey of which 34% were government health professionals and 24% were working with a research/academic institution. All participants were between 23 and 74 years age group (mean 39 years). Participants shared their views on first, knowledge about symptoms, preventive measures and treatment options for COVID-19. Second, on attitude towards handling COVID-19 pandemic using social distancing, following lockdown and travel advisory, etc. Third, on the practice of non-pharmaceutical measures to prevent COVID-19. We found that the social media platform acted as one of the most important platforms for awareness generation regarding COVID-19 but it was also generating stigma among people. Till the time of the survey, there is still a dearth of knowledge about social distancing and what it means, especially physical distance of 1–3 metres and correct usage of mask in different situations. Various important issues pertaining to infant feeding practices, mother and childcare and disposal of dead bodies of COVID infected persons require deliberations and awareness.